Condition‐dependent reproductive tactics in male smallmouth bass: evidence of an inconsistent birthdate effect on early growth and age at first reproduction. (5th April 2017) - Welsh, D. P.; Wiegmann, D. D.; Angeloni, L. M.; Newman, S. P.; Miner, J. G.; Baylis, J. R.
Abstract: Many animals exhibit alternative forms of reproductive behavior, the expression of which depends on individual condition or status. For instance, male smallmouth bass Micropterus dolomieu that are large early in life often build a nest and spawn for the first time at a young age and small body size, while males that are small early in life delay reproduction, invest in growth and spawn when they are older and larger, tactics referred to as α and β, respectively. The observation that larger males also tend to spawn earlier within a season led to a hypothesis that birthdate – more specifically, dispersal date – may control which tactic is adopted. Here, we examined the individual growth and reproductive histories of 184 male M. dolomieu of three cohorts for evidence of a birthdate effect on early life condition and the subsequent expression of tactics, namely whether a long first‐year growth period tends to induce the α tactic and whether variability in the timing of reproduction by parents within a season contributes to body size differences in progeny at the end of their first‐year growth period. The extent to which male condition early in life influences the expression of tactics was also evaluated. Evidence of a birthdate effect on progeny condition and subsequent tactic choice was observed for only one of the three cohorts and, in another cohort, tactic choice and individual condition were largely unrelated. The seasonal variability in birthdates and growth histories suggest that a broad range of swim‐up dates may be necessary to generate differences in condition early in life that are sufficiently large to control future reproductive decisions. Potential impacts of various physical, environmental and biotic factors that may mediate the seasonal timing of reproduction by parents or individual growth early in life are discussed. Abstract : In this study, we examined the individual growth and reproductive histories of 184 male smallmouth bass of three cohorts for evidence of a birthdate effect on early life condition and the subsequent expression of reproductive tactics, specifically the age at which males first reproduced. Evidence of a birthdate effect on progeny condition and tactic choice was observed for only one of the three cohorts and, in another cohort, tactic choice and individual condition were largely unrelated. The seasonal variability in birthdates and growth histories suggest that a broad range of swim‐up dates may be necessary to generate differences in condition early in life that are sufficiently large to exert strong control over future reproductive decisions.